Penambahan Katalik Konverter Plat Tembaga Berbentuk Spiral Terhadap Emisi Gas Buang Motor Bakar Menggunakan Gasboard 5020 - Daryono, Mohammad; Darmanto, Seno (universitas teuku umar, 2022)
Due to the high use of motorized vehicles, air pollution will arise which can interfere with the environment and human health. The results of the combustion of motor vehicle fuels produce pollutants that are harmful to human health, if inhaled by humans, they can cause respiratory tract irritation, eye irritation and skin allergies, which can lead to lung cancer. The purpose of this study was to examine whether copper plates can be used as a substitute for catalytic converters to reduce exhaust gas emissions (CO and HC gases). The test results show that copper plate can be used as a catalytic converter replacement material with a significant reduction in exhaust emissions, with a decrease in the percentage of CO by 29.9% at 5000 rpm using a 10 winding catalyst, and a decrease in the percentage of HC by 33.9% at rotation. 5000 rpm using a 10 winding catalyst. Suggestions from this study are if you use it for daily purposes, you should use a catalyst that has 10 winding.